A Systematic Review of Copper Heap Leaching: Key Operational Variables, Green Reagents, and Sustainable Engineering Strategies - León, Fabian (2025)
Heap leaching of copper is faced with a complex set of challenges, including mineral heterogeneity, the formation of passivating species, and the need to regulate critical variables such as pH, redox potential (Eh), oxidant concentration, and irrigation rate. If these factors are not properly managed, copper recovery is reduced, and significant environmental impacts may be generated, highlighting the urgency for systematic and sustainable approaches. To address this challenge, a systematic literature review (SLR) was conducted, screening 2344 documents and selecting 106 primary sources to analyze operational drivers and environmental considerations. Statistical methodologies (factorial designs, response surface methodology), multiscale modeling, and laboratory column tests were used to validate key variables, including pH (1.5–2.0), Eh (600–750 mV), temperature (25–55 °C), irrigation rate (5–15 L/(h·m2)), acid concentration (0.5–2.0 M), and emerging “green” reagents (e.g., glycine, organic surfactants). Precise control of these factors was found to reduce passivation, minimize fine-particle migration, and improve copper extraction up to 90%. The incorporation of oxidizing agents (e.g., Fe3+, H2O2) further accelerated mineral dissolution while preventing unwanted precipitates. In parallel, bioleaching strategies maintained high recoveries with lower chemical demand. Reviews of pilot studies confirmed the scalability of these optimized conditions, emphasizing both sustainability and cost-effectiveness.